Deep level transient spectroscopy characterisation of defects in AlGaN/Si dual‐band (UV/IR) detectors grown by MBE. Issue 1 (10th December 2012) - Aziz, M.; Mari, R. H.; Felix, J. F.; Mesli, A.; Taylor, D.; Lemine, M. O.; Henini, M.; Pillai, R.; Starikov, D.; Boney, C.; Bensaoula, A.
Abstract This paper is based on the investigation of electrically active defects in dual band UV/IR photodiodes using Deep Level Transient Spectroscopy (DLTS). The UV/IR photodiodes were fabricated by growing Al0.7Ga0.3N layers on silicon substrate to obtain UV‐ sensitive photodiode structures on the front side, whereas on the back side of silicon IR‐sensitive photodiode structures were fabricated. Our studies reveal the existence of two defect levels in each detector. In order to determine accurately the position of these levels within the band gap of the respective layers, Laplace DLTS has been employed. The activation energies of defects in the UV photodetectors are 0.11±0.01 eV, and 0.31±0.01 eV, whereas, those in the IR detector are 0.25±0.01 eV and 0.47±0.02 eV. These energies are with respect to the conduction band energy of each detector. The effect of the junction electric field on the carrier emission rates of the deep traps was investigated by applying the double pulse Laplace DLTS technique. In particular it is found that the activation energy of the defect in the IR detector (0.47±0.02 eV) changes with electric field. Therefore, in this paper we will present detailed DLTS and Laplace DLTS investigations of deep traps in detectors based on AlGaN/Si (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)